Avian Influenza Viruses in Water Birds, Africa - Gaidet, Nicolas (Centers for Disease Control and Prevention, 2007)
We report the first large-scale surveillance of avian influenza viruses in water birds conducted in Africa. This study shows evidence of avian influenza viruses in wild birds, both Eurasian and Afro-tropical species, in several major wetlands of Africa.